The Effect of Life Cycle on Financial Statement Comparability by Consideration Moderating Role of the Information Asymmetric - Sad saleh Sabah; Daruosh Foroghi; Seyed Abass Hashemi (پژوهش‌های تجربی حسابداری)
The purpose of the research is to investigate the effect of different stages of the firms's life cycle on the comparability of financial statements with regard to the role of information asymmetry. The statistical the population of this study are all companies listed in Tehran Stock Exchange, in which 100 companies in the period 2012 to 2023 have been selected by systematic elimination method. For data analysis and hypothesis testing, multivariate regression model based on panel data regression is used. The findings of the research showed that the comparability of financial statements is higher in the maturity stage than in other stages. Also, the findings showed that despite high information asymmetry, firm in the maturity stage are more inclined to present comparable financial statements. The findings of this research provide evidence that firms in the maturity stage are more comparable due to having an efficient accounting system, skilled human resources and strong internal control